Pengujian Lemari Pengering Menggunakan Kalor Outdoor Air Conditioner Split 2PK Menggunakan Penambahan Hair Dryer - Fuad Abdul Aziz; Sugeng Priyanto (ELASTICITY: Journal of Applied Engineering Science, 2024)
A dryer cabinet that functions to reduce the moisture content of substances/materials until you get low moisture content results. This drying process separates some of the liquid substances that are in a substance/material until the liquid content is reduced. In the industrial sector, especially home industries/MSMEs, dryers are very useful if the land for the drying process using sunlight is very limited, because dryers are more efficient in time and place. Especially with the addition of heat emitted by the hair dryer, it makes the drying process more efficient. The drying cabinet that we tested has a multifunction in terms of the drying process indoors or outdoors, depending on the placement of the Outdoor AC. This dryer cabinet is also a medium for using waste heat from outdoor air conditioning to minimize wasted heat. Therefore, the existence of outdoor air conditioning, ducting, drying cabinets, and the addition of hair dryers can help ease the drying process in the home industry.